E-Commerce Educational Flashcard Using Rapid Application Development (RAD) at Lantaburo Homeschooling - Mulyati Lestari; Ruci Maiyanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The advancement of information technology has significantly impacted various aspects of life, including the education sector. Homeschooling Lantaburo, as a provider of alternative education, requires an effective platform to support the learning process, particularly in providing interactive learning media such as flashcards. This study aims to develop an educational flashcard e-commerce platform using the Rapid Application Development (RAD) method to accelerate the creation and delivery of engaging and interactive learning tools. The RAD method was chosen for its ability to produce systems in a relatively short time through iterative processes and prototyping. The results of this study demonstrate that the development of an educational flashcard e-commerce platform was successfully implemented with features such as a product catalog, shopping cart, checkout, and a user-friendly payment system. System testing indicated that the platform performs well and delivers positive user experience. In conclusion, the application of flashcard e-commerce using the RAD method is effective in facilitating accessible educational flashcard purchases and enhancing the quality of teaching and learning processes at Homeschooling Lantaburo